Pemberdayaan Ekonomi Masyarakat Berbasis Ekonomi Kreatif Di Desa Wanakerta Kec. Bungursari Purwakarta - Damiri, Ahmad; Jalaludin, Jalaludin; Susanti, Tri; Setiawati, Ayu Fajar (STIE Syariah Indonesia Purwakarta, 2021)
This shift in the orientation of the world economy that prioritizes human resource assets has led to extraordinary competition in the creative world (global competition of talents). Rural development through agricultural industrialization or increasing food production based on regional development and based on economic growth. Wanakerta Village, Bungursari Sub-district, Purwakarta Regency is a village based on agriculture and plantations, and several potentials exist for Micro and Small Enterprises including character lamp craftsmen, Bead Bags, and Banana Chips. And at this time in the village it is very necessary for appropriate business developments. The implementation of community assistance and development is one of the goals of PKM activities which are expected to be able to solve problems that exist in the Wanakerta Village community, both in the economic, religious, social and cultural fields, village government, as well as in the fields of education and health. Through assistance to the community, this PKM activity collects data on problems or conditions of the surrounding community which is then formulated in the form of a work program and its realization which is expected to answer problems that exist together with the community. Then the formulated work program has been realized approximately 90% according to the ability of PKM participants, although there are still obstacles in its implementation.